Market power and fiscal policy in OECD countries - Afonso, António (2022)
We compute average markups as a measure of market power throughout time and study their interaction with fiscal policy and macroeconomic variables in a VAR framework. From impulse-response functions, the results, with annual data for a set of 14 OECD countries, show that the markup (i) depicts a pro-cyclical behaviour with productivity shocks and (ii) a counter-cyclical behaviour with fiscal spending shocks. We also use a PVAR, increasing the efficiency in the estimations, which confirms the country-specific results.